The Study of the Effects of us Geopolitical Policies on the Divergence of the Islamic World. Case Study: Southwest Asia - Afzali, Rasoul; Seyedi Asl, Seyedmohammad (Wydawnictwo Naukowe Wydziału Nauk Politycznych i Dziennikarstwa Uniwersytetu im. Adama Mickiewicza w Poznaniu, 2022)
The Islamic world is one of the most important regions in the world in terms of geopolitical competition, focusing on the region of Southwest Asia in terms of geo-economic, geo-strategic and geo-culture. Despite the widespread commonalities in the political geography of the Islamic world in structural and functional terms, the interdependence of the region has not been able to move towards convergence, cooperation and interaction. One of the influential variables in the political trends of this region has been the geopolitical policies of the United States of America. The United States has always influenced the political trends of this strategic region based on its goals and interests. The result of researches show that the United States has a significant impact on divergence of Islamic world in terms of geo-culture in promoting the discourse of liberalism, geo-strategy on arms sales and stabilization of military rivalries between world powers, and geo-economics in free market competition and cheap energy resources. The convergence of Islamic world has been against the geopolitical interests of the United States of America.

Obszarem zainteresowania autora stał się region Azji Południowo-Zachodniej. Został on poddany analizie ze szczególnym uwzględnieniem czynników geoekonomicznych, geostrategicznych oraz geokulturowych. Pomimo szeroko rozpowszechnionych podobieństw w geografii politycznej świata islamu pod względem strukturalnym i funkcjonalnym, czynniki te okazały się niewystarczające aby wspomniany obszar zmierzał w kierunku konwergencji, współpracy i interakcji. Jedną z istotnych zmiennych mających ogromny wpływ na region była polityka Stanów Zjednoczonych Ameryki. USA współkształtując trendy polityczne tego strategicznego regionu kierowały się swoimi celami strategicznymi oraz interesami. Zdaniem autorów Stany Zjednoczone mają znaczący wpływ na dywergencję świata islamu w zakresie geokultury – poprzez promowanie dyskursu liberalnego, geostrategii – poprzez sprzedaż broni i utrzymywanie rywalizacji militarnej między światowymi mocarstwami oraz geoekonomii – poprzez utrzymywanie wolnorynkowej konkurencji i niskich cen surowców energetycznych. Autorzy podkreślają, iż ich zdaniem konwergencja świata islamu była sprzeczna z geopolitycznymi interesami Stanów Zjednoczonych Ameryki.
Badanie wpływu paradygmatu geopolitycznego w polityce zagranicznej USA na dywergncje w obrębie świata Islamu. Studium przypadku Azji Południowo-Zachodniej
Keywords: Geopolitics; United States; Divergence; the Islamic World; Southwest Asia; geopolityka; Stany Zjednoczone; dywergencja; świat islamski; Azja Południowo-Zachodnia